MANAJEMEN PENDIDIKAN DAN PELATIHAN PENDAMPING PKH (PROGRAM KELUARGA HARAPAN) BERBASIS BLENDED LEARNING - Iwan Kurniawan (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the description of training and education management PKH Based on Blended Learning in BBPPKS Bandung. The management of this training includes the planning, implementation, and evaluation stages. This research is a descriptive study with a qualitative approach. Data collection techniques in this study through interviews, document study, and observation. The validity of the data was checked by triangulation. The results showed that the training and education management PKH Based on Blended Learning includes: 1) Planning which includes analysis of training needs, preparation of training objectives, preparation of training plans, and preparation of administration; 2) The implementation of this training stage includes online learning, opening, offline learning and training closing; 3) Evaluation which consists of four forms of evaluation, namely evaluation of training participants, evaluation of lecturers, evaluation of the implementation of education and training and evaluation of post-training. In addition, training and education PKH Based on Blended Learning is also influenced by the availability of the internet network, the seriousness of the training participants, the mastery of technology owned by the participants, the PBL location, the readiness of the organizers, the completeness. infrastructure, and availability of costs.